Adaptive density-based spatial clustering of applications with noise (DBSCAN) according to data - Wei-Tung Wang; Yi-Leh Wu; Cheng-Yuan Tang; Maw-Kae Hor (2015 International Conference on Machine Learning and Cybernetics (ICMLC), 2015)
Clustering is a task that aims to grouping data objects into several groups. DBSCAN is a density-based clustering method. However, it requires two parameters and these two parameters are hard to decide. Also, DBSCAN has difficulties in finding clusters when the density changes in the dataset. In this paper, we modify the original DBSCAN to make it able to determine the appropriate eps values according to data distribution and to cluster when the density varies among dataset. The main idea is to run DBSCAN with different eps and Minpts values. We also modified the calculation of the Minpts so that DBSCAN can have better clustering results. We did several experiments to evaluate the performance. The results suggest that our proposed DBSCAN can automatically decide the appropriate eps and Minpts values and can detect clusters with different density-levels.